Psychological Adaptive Mechanism Maturity Predicts Good Outcomes in Treatment for Refractory PTSD - Beresford, Thomas; Wahlberg, Lawrence; Hipp, Daniel; Ronan, Patrick J. (Frontiers in Psychology, 2021)
Background: PTSD severity follows a bell-shaped curve ranging from mild to severe. Those in the severe range often receive the most intensive treatments, including targeted residential rehabilitation stays. These are expensive and welcome ways to improve their effectiveness. We hypothesized that positive change among subjects treated in a 45-day residential rehabilitation format would be associated with the maturity levels of measurable Psychological Adaptive Mechanisms (PAMs), alternately ego defense mechanisms. Methods: In this association study, adult male patients (N=115) with a history of combat related PTSD treated in a residential rehabilitation setting completed the Defense Style Questionnaire (DSQ) on admission, as well as the Post-Traumatic Stress Disorder Checklist – Military Version (PCL-M) and the Mississippi Scale for Combat-Related Posttraumatic Stress Disorder (M-PTSD) on admission and again at discharge. This allowed prospectively calculated change scores on each of the PTSD measures for each patient. The change scores allowed association testing with averaged admission DSQ scores using Pearson's correlation probability with significance held at p<0.05. Results: As hypothesized, averaged individual Mature scores on the DSQ were associated with improved change scores on both the PCL-M (p=0.03) and the M-PTSD (p=0.04). By contrast neither averaged DSQ Neurotic or Immature scores associated significantly with either PTSD scale change scores. Conclusion: These results, the first of their kind to our knowledge, suggest that patients presenting with predominantly Mature level PAMs are likely to benefit from residential rehabilitation treatment of PTSD. By contrast, those presenting with Neurotic or Immature PAMs predominantly are less likely to encounter positive change in this type of treatment. Although residential treatment is often reserved for the most refractory PTSD cases, it appears that those endorsing Mature level PAMs will make use of residential treatment whereas other forms of treatment may be better suited to those with Neurotic and Immature adjustment mechanisms.